Author Correction: Nearly all the sky is covered by Lyman-α emission around high-redshift galaxies. (29th November 2018) - Wisotzki, L.; Bacon, R.; Brinchmann, J.; Cantalupo, S.; Richter, P.; Schaye, J.; Schmidt, K.; Urrutia, T.; Weilbacher, P.; Akhlaghi, M.; Bouché, N.; Contini, T.; et al.
Change history: In this Letter, author M. Akhlaghi should be associated with affiliation (2) rather than (3). This error has been corrected online.